Transcriptome analysis and molecular characterization of novel small RNAs in Mycobacterium tuberculosis Lineage 1 - Mohd Iskandar Jumat; Chin, Kai Ling (Springer Nature, 2024)
Mycobacterium tuberculosis (Mtb), the tuberculosis-causing agent, exhibits diverse genetic lineages, with known links to virulence. While genomic and transcriptomic variations between modern and ancient Mtb lineages have been explored, the role of small non-coding RNA (sRNA) in post-translational gene regulation remains largely uncharted. In this study, Mtb Lineage 1 (L1) Sabahan strains (n=3) underwent sRNA sequencing, revealing 351 sRNAs, including 23 known sRNAs and 328 novel ones identified using ANNOgesic. Thirteen sRNAs were selected based on the best average cut-off value of 300, with RT-qPCR revealing significant expression differences for sRNA 1 (p=0.0132) and sRNA 29 (p=0.0012) between Mtb L1 and other lineages (L2 and L4, n=3) (p>0.05). Further characterization using RACE (rapid amplification of cDNA ends), followed by target prediction with TargetRNA3 unveils that sRNA 1 (55 base pairs) targets Rv0506, Rv0697, and Rv3590c, and sRNA 29 (86 base pairs) targets Rv33859c, Rv3345c, Rv0755c, Rv0107c, Rv1817, Rv2950c, Rv1181, Rv3610c, and Rv3296. Functional characterization with Mycobrowser reveals these targets involved in regulating intermediary metabolism and respiration, cell wall and cell processes, lipid metabolism, information pathways, and PE/PPE. In summary, two novel sRNAs, sRNA 1 and sRNA 29, exhibited differential expression between L1 and other lineages, with predicted roles in essential Mtb functions. These findings offer insights into Mtb regulatory mechanisms, holding promise for the development of improved tuberculosis treatment strategies in the future.